Study on prevention and control mechanism of runoff water hazard in thick coal seam mining in valley terrain - Zhang, Yunfeng; Qian, Chenlong; Wang, Xufeng; Chen, Xuyang; Chang, Zechao; Wang, Jiyao; Niu, Zhijun (Frontiers in Earth Science, 2023)
During the mining of thick coal seams under the gully slope, the mining-induced fractures are prone to connect with the gully runoff, which may induce potential water hazards and affect underground production. Based on the occurrence characteristics of coal seams and the landform in the gully-developed mining area, the coal seam mining under the slope of Na'er Coal Mine and Baoshan Coal Mine was taken as the engineering background, the seasonal runoff of gullies was considered as the influencing factors of the safe mining, and the spatial relationship between the working face and the gully slope was analyzed when the mining-induced fractures were connected with the gully surface and caused the gully runoff water disaster. The research results show that the occurrence structure of the gully slope has a greater impact on the strata movement of the slope. When the key layer is incomplete, the horizontal sliding and local block overturning of the slope rock strata are strong; when the key layer is complete, the horizontal sliding and local block overturning of the slope rock strata are weakened. According to the safety distance of the working face and the generalized model of safety coal pillar setting, the method of setting the safety coal pillar was used to prevent the connection of slipping cracks of the rock strata at the slope bottom and the gully surface during the slope mining, thus preventing the occurrence of runoff hazards during the thick coal seams mining in the valley terrain. The results can provide a theoretical basis and technical support for the prevention and control of seasonal runoff hazards, as well as a reference for the prevention and control of mining-induced landslides, water conservation mining, and ecological environment protection.